EFFECT OF PRICE AND PROMOTION ON CAR PURCHASE DECISIONS - Syamsu Rijal; Mawardi Mawardi; Uli Wildan Nuryanto; I Nyoman Tri Sutaguna; Endang Fatmawati (Journal of Innovation Research and Knowledge, 2023)
The purpose of this research is to analyze effect of price and promotion on car purchase decisions. The type of research used is a type of quantitative research. In this study, the population used was all consumers who purchased Toyota cars in Medan, but the exact sample size was unknown. So the minimum number of samples taken in this study is 18 times 5 to 90 respondents. In this study using data collection methods with field research and library research. Data analysis in this study uses multiple linear regression analysis. The results of the study show that price has a positive and significant effect on car purchase decisions. Promotion has a positive and significant effect on car purchase decisions.